Obtaining diffuse scattering patterns from computer simulations – a retrospective. Issue 3 (20th April 2022) - Welberry, T. R.
Abstract : The paper describes how the calculation of diffuse scattering from atomistic model crystals has developed over the last approximately 50 years. Abstract : The paper describes how the calculation of diffuse scattering from atomistic model crystals has developed over the last approximately 50 years. Not only has the quality of observed diffuse X‐ray scattering data improved immensely with the advent of electronic area detectors and synchrotron radiation but the enormous increase in computer power has enabled patterns, of comparable quality to the observations, to be calculated from a Monte Carlo model.